Информационные воздействия и безопасность на транспорте = The information actions and safety on the transport - E. V. Klymentova; V. V. Klymentov; W. A. Zukow (Kazimierz Wielki University, 2015)
Klymentova E. V., Klymentov V. V., Zukow W. Информационные воздействия и безопасность на транспорте = The information actions and safety on the transport. Journal of Education, Health and Sport. 2015;5(6):304-312. ISSN 2391-8306. DOI 10.5281/zenodo.18617 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A304-312 https://pbn.nauka.gov.pl/works/566858 http://dx.doi.org/10.5281/zenodo.18617 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015.   ИНФОРМАЦИОННЫЕ ВОЗДЕЙСТВИЯ И БЕЗОПАСНОСТЬ НА ТРАНСПОРТЕ THE INFORMATION ACTIONS AND SAFETY ON THE TRANSPORT   Е. В. Климентова, В. В. Климентов, В. Жуков E. V. Klymentova, V. V. Klymentov, W. Zukow   Киевский национальный университет имени Тараса Шевченко, Украина Научный парк «Профилактическая медицина и охрана труда - новейшие  системы и технологии», Одесса, Украина Taras  Shevchenko National University of Kyiv, Ukraine Science park "Preventive Medicine and Labour Protection -The newest systems and technologies", Odessa, Ukraine Kazimierz Wielki University, Bydgoszcz, Poland   Abstract The article deals with the peculiarities of function of the system: man - transport - road in new information conditions of nowadays. The verbal suggestive potential is implemented in the audio signals, which broad casting by radio canal, have been described. The verbal forms of manipulation influence lead to the formation of special brain status, which decreases the control attention of a driver and actives right cerebral hemisphere. Such effects are very dangerous and undesirable for any driver. They cause new risks for safety on the roads. Understanding of the programming character|nature| of the verbal information, correlation of language manipulations and cerebral regulation of a driver let us reconstruct conception of safety on the roads. Key words: safety on the roads, information influence, verbal suggestive influence, audio signals, transport.   Реферат В статье рассматривается специфика функционирования системы: человек - транспорт - дорога в новых информационных условиях современного этапа. Анализируется вербально-суггестивный потенциал, имплементированный в аудио сигнал, который поступает по радиоканалу. Вербальные формы манипулятивного влияния формируют особое состояние мозга, которое характеризуется снижением контролирующего внимания водителя и активизацией правого полушария мозга. Эти эффекты очень опасны и нежелательны для любого водителя. Они становятся причиной формирования новых рисков для безопасности на дорогах. Понимание программирующего характера вербальной информации, корреляция языковой манипуляции с мозговой активностью водителя позволяет нам пересмотреть концепцию безопасности на дорогах. Ключевые слова: безопасность на дорогах, информационное влияние, вербальное суггестивное влияние, аудиосигнал, транспорт.